A three-valued photoelectrochemical logic device realising accept anything and consensus operations1. Issue 17 (28th February 2015) - Warzecha, M.; Oszajca, M.; Pilarczyk, K.; Szaciłowski, K.
<x xml:space="preserve">Abstract</x> A new application of a hybrid material exhibiting the photoelectrochemical photocurrent switching (peps) effect in a three-valued logic device is reported.